Bend family proteins mark chromatin boundaries and synergistically promote early germ cell differentiation. Issue 10 (3rd November 2021) - Shi, Guang; Bai, Yaofu; Zhang, Xiya; Su, Junfeng; Pang, Junjie; He, Quanyuan; Zeng, Pengguihang; Ding, Junjun; Xiong, Yuanyan; Zhang, Jingran; Wang, Jingwen; Liu, Dan; et al.
Abstract: Understanding the regulatory networks for germ cell fate specification is necessary to developing strategies for improving the efficiency of germ cell production in vitro . In this study, we developed a coupled screening strategy that took advantage of an arrayed bi-molecular fluorescence complementation (BiFC) platform for protein-protein interaction screens and epiblast-like cell (EpiLC)-induction assays using reporter mouse embryonic stem cells (mESCs). Investigation of candidate interaction partners of core human pluripotent factors OCT4, NANOG, KLF4 and SOX2 in EpiLC differentiation assays identified novel primordial germ cell (PGC)-inducing factors including BEN-domain (BEND/Bend) family members. Through RNA-seq, ChIP-seq, and ATAC-seq analyses, we showed that Bend5 worked together with Bend4 and helped mark chromatin boundaries to promote EpiLC induction in vitro . Our findings suggest that BEND/Bend proteins represent a new family of transcriptional modulators and chromatin boundary factors that participate in gene expression regulation during early germline development.